Optimization of the forward extraction of jacalin from jackfruit (artocarpus heterophyllus) seed crude extract by AOT reverse micelles - Sharifah Fathiyah, Sy Mohamad; Farhan, Mohd Said; Mimi Sakinah, A. M.; Shahril, Mohamad; Wan Mohd Azizi, Wan Sulaiman (2019)
Jacalin is the major protein contained in the crude extract of jackfruit seed that specifically recognizes and binds reversibly to galactose. Currently, purification of jacalin is carried out using the tedious and costly chromatographic techniques. Therefore, in this study, we applied the reverse micellar extraction, an alternative method widely used for downstream processing of various proteins. A successful reverse micellar extraction consists of two basic steps: forward and backward extraction. Forward extraction transfers a target protein from an aqueous solution into the reverse micellar solution, while backward extraction releases the protein from the reverse micelles structure into a new aqueous solution. We optimized the main parameters influencing the extraction of jacalin from the crude extract of jackfruit seed using the sodium bis(2-ethylhexyl) sulfosuccinate (AOT) reverse micellar system. The effects of the aqueous phase pH, NaCl concentration and AOT concentration on the forward extraction efficiency (FEE) are investigated using the response surface methodology (Box-Behnken Design). The adequacy of the Box–Behnken response surface model for predicting the FEE is verified using regression analysis. The main effects and interactions of the significant parameters are analyzed through the 3D surface plots. The optimum forward extraction conditions were determined as follows: aqueous phase pH 4.58, 125 mM NaCl and 40 mM AOT. Under the optimal conditions, the FEE reached 88.04±1.30%, closer to 87.99 % predicted by the model. In conclusion, the AOT/isooctane reverse micellar system is highly effective to extract jacalin from the jackfruit seed and verified the suitability of the BBD approach to optimize the parameters in the forward extraction process.